Sustainability impact assessment of trade policy and its application in the context of Latin America - Blanco, Hernán (2006)
Reviews some theoretical and practical aspects of the sustainability impact assessment (SIA) of trade agreements and policies, in order to make recommendations that would contribute to its application in Latin America. Argues for the implementation of SIA in developing countries.